Pengaruh Tingkat Suku Bunga, Pertumbuhan Penjualan dan Kebijakan Dividen terhadap Harga Saham - Rika Amelia; Dea Annisa (Indonesian Journal Publisher, 2025)
This study aims to test whether interest rates, sales growth and dividend policy affect stock prices in consumer cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) in 2021 to 2023. The type of research conducted is quantitative research using the associative method. The research sample was determined using a purposive sampling technique, so that it can produce a sample of 15 companies with a total of 45 observation data. The analysis tests used were descriptive statistical analysis tests, selection of panel data regression models, classical assumption tests, panel data regression analysis and hypothesis tests. The results of the study prove that interest rates, sales growth and dividend policies have been proven to affect stock prices.